PERSPSI PETUGAS PENDAFTARAN TERHADAP SIMETRISS DI BAGIAN RAWAT JALAN RSUP Dr. SARDJITO YOGYAKARTA - Gamassiano Alfiansyah; Safira Marahastadarta (Politeknik Negeri Jember, 2021)
User perception is very important in assessing the performance of a system. A person's attitude towardsinformation systems shows how far the person feels that the information system is good or bad. This meansthat the more involved the system user, the more positive the system will be. In February, there was a problemwith SIMETRISS in the outpatient registration section, which is often a disruption in the network that results inloading too long to input patient data. This type of research is qualitative. Data collection techniques in the formof interviews and observations. The subject of this study was the registration officer in the outpatient section.The results of this report are the perceived usefulness indicators that the performance of SIMETRISS, if thereis trouble on the network, makes the staff stop to continue their work and waits for the IT staff to solve itimmediately. Most of the respondents answer the Perceived Ease of Use indicator saying that they havedifficulties in serving patients if there is trouble during service hours because they can not access SIMETRISSto check the patient's history and membership status, and the attitude indicator (attitude toward using), if thereis a very long response time, it will make the officer stop to register the patient because response time is verylong and SIMETRISS is inaccessible, at last it will make the patient wait a long time and may cause buildup onregistration. Suggestions can be taken, the insti (Information Technology Installation) should immediately dealwith the problem because it can cause patients to wait a long time and there is a buildup of patients at theregistration and maintenance needs to be done routinely and periodically with a period of 3 or 6 months.